Advanced oxide dispersion strengthened and nanostructured ferritic alloys. (1st October 2013) - Miller, M. K.; Parish, C. M.; Li, Q.
<x xml:space="preserve">Abstract</x> Nanostructured ferritic alloy is a subcategory of oxide dispersion strengthened steels intended for advanced reactor applications. The complex ultrafine grained microstructure of an advanced nanostructured ferritic alloy, as determined by electron microscopy and atom probe tomography, is summarised. Three distinct populations of precipitates were observed: 20-50 nm Ti(N, O, C), 5-10 nm diameter Y2Ti2O7/Y2TiO5 and 1-4 nm diameter Ti, Y, O enriched nanoclusters. The first two populations were predominantly located along grain boundaries together with Cr, W and C segregation. A dense population of nanoclusters was observed both in the grain interior as well as on the grain boundaries. These nanoclusters are highly tolerant to high dose irradiation at elevated temperatures.